2021
DOI: 10.1111/jfpe.13858
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of physical and aerodynamic properties of corn kernel (KSC 704)

Abstract: Physical and aerodynamic properties of agricultural products have been used to precision design of the machinery and different postharvest operations. In this study, some physical and aerodynamic properties of corn kernels were investigated as a function of size at three levels of small, medium, and large (8.41 mm, 9.60 mm, and 11.62 mm, respectively) and moisture content in the range of 10 to 25% (wet basis). According to results, with increasing the moisture content from 10 to 25%, the length; width; thickne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…When the sample starts to slide down, the ruler is used to record the tilt angle. The coefficient of friction can be calculated by the formula given as follows 8 , 15 : where μ—the coefficient of friction, α —the tilt angle (°).…”
Section: Methodsmentioning
confidence: 99%
“…When the sample starts to slide down, the ruler is used to record the tilt angle. The coefficient of friction can be calculated by the formula given as follows 8 , 15 : where μ—the coefficient of friction, α —the tilt angle (°).…”
Section: Methodsmentioning
confidence: 99%
“…The mainstream "roller plucking" mainly pulls corn cobs off the plant through a number of pairs of relatively rotating plucking rollers. During the process, the highspeed rotating cob picking rollers are in direct contact with the cobs, which can easily lead to serious cob injuries, kernel drop, and high breakage rate [28]. Geng A, et al found that the impact force on the cobs in cob picking increases with the increase in cob diameter and the decrease in the gap of the cob picking rollers.…”
Section: Mechanical Breakagementioning
confidence: 99%
“…Thus, a certain range of airflow velocity is required to simultaneously satisfy both conditions. Terminal velocities are the most significant properties in aerodynamics, and the terminal velocity at which the particles are suspended stationarily in the vertical air stream can be determined by using different methods: the free-fall, vertical air tunnel, and elutriator methods [17][18][19][20][21][22][23][24][25][26][27][28]. In this work, the custom-made device illustrated in Figure 1 was used to measure the terminal velocity of the different outputs of the threshing system, and to provide the basic information for designing a cleaning device.…”
Section: Terminal Velocity Test-bed For Each Threshing Output Componentmentioning
confidence: 99%